IMPLEMENTING HANDS-ON METHODS TO IMPROVE STUDENTS' ENGLISH PROFICIENCY - Yani Lubis; Hapni Hasibuan; Mutiah Nasution; Viola Chairani Putri; Hadi Purnomo; Panji Kesuma (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research aims to implement a direct method in improving students' English skills. The hands-on method is known as a teaching approach that focuses on using the target language directly in the learning process. This research is a type of research that collects data from literature. The data collection technique in this study is documentation, namely looking for written sources that contain information on the topics discussed. The results show that the application of the direct method is effective in improving students' English comprehension and skills, as well as increasing their motivation in learning. The implication of this study is the importance of applying direct methods in an educational context to support students' English communication skills holistically.